Consideraciones sobre la aplicación del principio iura novit curia en el arbitraje comercial internacional (2014)
Despite its recognition in different jurisdictions, the application of the iura novit curia principle in international commercial arbitration has been subject to debate. From the most liberal point of view, the principle is entirely applicable to international commercial arbitration in the same way that it would be applied by a judge when rendering a decision under his national law. However, from the most conservative standpoint, any manifestation of this principle allowing arbitrators to take the initiative in raising new legal issues during the proceedings must be completely rejected. Taking as a premise that, generally speaking, members of an international arbitral tribunal are not familiar with the law applicable to the disputes that are brought to them and that they have no experience or practical knowledge regarding such law, the application of the iura novit curia principle in its purest form would not be adequate in the context of international commercial arbitration given its contractual nature and the interests involved. On the other hand, an outright rejection of this principle in international commercial arbitration would tie the hands of arbitrators and create the risk of awards being rendered that either ignore or contradict rules or principles that form part of the applicable law, which could lead to challenges to their validity or later enforcement. For this reason, in order for iura novit curia to be applied in the context of international commercial arbitration, an intermediate approach should be adopted. This involves a significant adaptation of the principle, so that some of its manifestations could be accepted in exceptional circumstances as a tool that arbitrators could use in order to fully comply with duties that are inherent to their decision-making function, including the duty not to exceed the jurisdiction conferred upon them by the parties, the duty to render awards that are valid, enforceable and in accordance with the applicable law, the duty to act in an impartial manner and the duty to guarantee at all times fundamental due process rights of the parties, such as the right to adequately and timely exercise their defense and the right to equality.